The fragile upper subject: Gender, digital discourse, and superego collapse in contemporary Indonesian media - Udasmoro, Wening; Marai, Leo; Firmonasari, Aprillia (Program Studi Ilmu Komunikasi, 2026)
Studies have been exploring the processes of identity construction increasingly intertwined with the behaviors of netizens. The construction of self-identity is now entangled with global capitalism. The contribution of this article is the exploration of the Superego as a site of vulnerability in the age of social media. In the current media environment, this vulnerability of the Superego is observable through the figure of the prominent individual whose visibility, amplified by significant social capital, draws both admiration and hostility from followers. This paper introduces the concept of the Upper Subject to understand such figures. This study focuses on two political figures who can be categorized as Upper Subjects based on the number of followers they command on social media: Khofifah Indar Parawansa (the Governor of East Java) and Dedi Mulyadi (the Governor of West Java). Both serve as the primary subjects of this analysis. The study adopts a Critical Discourse Analysis (CDA) method to examine how these Upper Subjects are constructed and contested within digital discourse.